2015
DOI: 10.1007/s12020-015-0796-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and diagnostic approach to patients with hypopituitarism due to traumatic brain injury (TBI), subarachnoid hemorrhage (SAH), and ischemic stroke (IS)

Abstract: The hypothalamic-pituitary dysfunction attributable to traumatic brain injury (TBI), aneurysmal subarachnoid hemorrhage (SAH), and ischemic stroke (IS) has been lately highlighted. The diagnosis of TBI-induced-hypopituitarism, defined as a deficient secretion of one or more pituitary hormones, is made similarly to the diagnosis of classical hypopituitarism because of hypothalamic/pituitary diseases. Hypopituitarism is believed to contribute to TBI-associated morbidity and to functional and cognitive final outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 78 publications
0
20
0
3
Order By: Relevance
“…Hypopituitarism is a severe complication induced by TBI that causes affective disorder, cognitive dissonance, and physical symptoms; e.g., depression, anxiety, memory and concentration deficits, and fatigue 5 . In recent years, there has been an increasing amount of strong evidence that suggests that patients with TBI are at considerable risk of dysfunction of the hypothalamic-pituitary axis, and this risk is associated with morbidity and possibly mortality 69 . Furthermore, clinical trials have demonstrated that treatment with replacement hormones is convenient and physiologically relevant 9, 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypopituitarism is a severe complication induced by TBI that causes affective disorder, cognitive dissonance, and physical symptoms; e.g., depression, anxiety, memory and concentration deficits, and fatigue 5 . In recent years, there has been an increasing amount of strong evidence that suggests that patients with TBI are at considerable risk of dysfunction of the hypothalamic-pituitary axis, and this risk is associated with morbidity and possibly mortality 69 . Furthermore, clinical trials have demonstrated that treatment with replacement hormones is convenient and physiologically relevant 9, 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, clinical trials have demonstrated that treatment with replacement hormones is convenient and physiologically relevant 9, 10 . According to one report, the incidence of hypothalamic-pituitary dysfunction induced by TBI is 5.4% to 90% 6 . Mechanisms have been suggested regarding the factors of hypopituitarism caused by TBI, including primary injury to the hypothalamic–pituitary axis and/or to its blood supply and secondary damage caused by oxidative stress or compression of the hypothalamic–pituitary structure by cerebral edema, cerebral hemorrhage, and intracranial hypertension 4, 1114 .…”
Section: Introductionmentioning
confidence: 99%
“…TBI leading to hospitalization has an incidence of 100–350 per 100,000 in the general population [15], [16], [17], [18], [19]. Relatively few cases are fatal; most individuals survive long-term, some of whom continue to suffer from non-specific symptoms such as depression, fatigue, sexual disturbances, cognitive deficits and sleep disorders [20], [21]. More recent studies have reported a high prevalence of chronic anterior pituitary hormone deficiency following TBI with an estimated frequency of more than 25% (approximately 5% for CH) (Table 1) [17].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, hypopituitarism seems to be less frequent in stroke patients than in patients after TBI or SAH 54 . Despite the impact of stroke on morbidity and mortality, research on hypopituitarism after stroke has been very limited in recent years 55 . Moreover, hypopituitarism may rarely occur after infectious diseases like encephalitis or meningitis 56 , 57 and should be considered in these patients presenting with an unusual course.…”
Section: Acquired Hypopituitarism Due To Brain Traumamentioning
confidence: 99%